Extração por ponto nuvem do fungicida carbendazim em amostras de morango e detecção eletroquímica com eletrodo de DDB - Amorim, Kamila Pereira de (Universidade Federal de Catalão, 2021)
The cloud point extraction method (CPE) was used for the determination of the fungicide Carbendazim (CBZ) in commercial strawberry samples and the combination of electrochemical detection and high performance liquid chromatography (HPLC-EC) techniques was used for the determination of the extracted CBZ. A cathodically pre-treated boron doped diamond electrode (BDD) was used as the electrode material for all electrochemical determinations. The optimum chromatographic parameters resulted in a mobile phase composition of KH2PO4 (0,01 mol L-1; pH 4,0) / ACN (75:25 V/V) flow rate of 0,8 mL min-1. The potential applied for the electrochemical detection of 1,4 V x Ag/AgCl (3,00 mol L-1KCl) was selected from the constructed hydrodynamic voltamogram, varying the potential between1,0 V and 1,45 V x Ag/AgCl (3,00 mol L-1KCl). The efficiency of the extraction process was made by varying the pH of the commercial strawberry samples in a range from3,0 to 8,0, being the best result referring to the higher CBZ current signal obtained atpH 7,0.he variables temperature, ultrasonic bath time, mass of NaCl and amount of surfactant were investigated through Factor Planning 24 and central compound analysis (CCD), as the best conditions were: 40 ° C, 15 min, 0.6 g of NaCl and 1mL of 14% Tergitol® (% V / V). The LOD (S / R = 3) of 0.156 µmol L-1 and LOQ (S / R = 10) of 0.312 µmol L-1, were removed for the fungicide carbendazim without the EPN process. The LOD and LOQ values ​​of CBZ in strawberries, converted using FC (9.12) were 6.54 µg L-1 (34.2 nmol L-1) and 13.1 µg L-1 (68.4 nmol L-1), respectively. The validation of the method was carried out based on intra-day and inter-day recovery tests, with accuracy, precision and repeatability being evaluated. The proposed method was proposed in commercial strawberry of three criteria from the city of Catalão. In addition, the strawberry washing method was also tested, with 0.1% (w / v) sodium bicarbonate being more efficient. The electrochemical determination of CBZ extracted from strawberry samples was also performed using a batch injection system (BIA) and the results obtained proved to be promising (the gain in analytical signal compared to HPLC-EC was almost one hundred times greater). However, some limitations were found due to the presence of surfactant in the analyzed samples which when accumulated, resulted in the formation of bubbles/foam in the system.
Cloud point extraction of carbendazim fungicide in strawberry samples and electrochemical detection with BDD electrode
Keywords: Extração por ponto nuvem; eletrodo de diamante dopado com boro; detecção eletroquímica; carbendazim; morango; 1.06.03.02-6 Eletroquímica